PERLINDUNGAN ANAK DALAM PERSPEKTIF HAK ASASI MANUSIA - Alvian Tri Ramadhan; Muhamad Chaidar (Fakultas Ilmu Sosial dan Humaniora, 2025)
Protection of children is the obligation of both guardians, as well as the family and the encompassing community since the assurance given to children is to secure and ensure children and to fulfill children's rights to be able to live, create and develop so that they can socialize within the encompassing environment or region because children may be a blessing and blessing from God All-powerful which we must ensure and watch with all our hearts. The shape of child assurance in worldwide relations has been controlled within the Tradition on the Rights of the Child so that children must be ensured and ensured so that they can survive, develop, develop and be able to realize in an exertion to get able and quality instruction and the part of the government and the common open in directing children is required. and endeavor for legitimate assurance against acts of viciousness against children in arrange to move forward the welfare of children and make assurance by guaranteeing legitimate controls and the capacities of children's teach that are executed.